Fraudulent Financial Reporting and the Fraud Pentagon: Corporate Governance as a Moderator in the Financial Sector - Zamzam, Irfan; Ivanka, Vivi; Ohorella, Rizki Wahyu Utami; Zainuddin, Zainuddin (International Journal of Economics, Business and Innovation Research, 2025)
This study examines the influence of the fraud pentagon dimensions (Pressure, Opportunity, Rationalization, Competence, Arrogance) on fraudulent financial statement within the financial industry, with good corporate governance (GCG) as a moderating variable. Data were collected from the annual financial reports of financial sector companies listed on Indonesia Stock Exchange (IDX) for the period 2019-2023 and analyzed using Moderated Regression Analysis (MRA) with Eviews, The findings reveal that Pressure and Rationalization affect fraudulent financial statements, while Opportunity, Competence, and Arrogance do not have significant impacts. Furthermore, GCG fails to moderate the relationship between the fraud pentagon dimensions and fraudulent financial statements. This study extends the fraud pentagon theory and offers practical insight for companies to enchance internal controls and for regulators to develop more effective policies for preventing fraudulent financial statement in the financial indutry.